2009
DOI: 10.1007/s11192-008-2149-x
|View full text |Cite
|
Sign up to set email alerts
|

How old is the Web? Characterizing the age and the currency of the European scientific Web

Abstract: The aim of this paper is to model and study the age of the Web using a sample of about four million of web pages from the 16 European Research Area countries obtained during 2004 and 2005. Web page time-stamp (date when the web pages were created or last changed for last time), format and size in bytes data have been analysed. Several indicators are introduced to measure longitudinal aspects of the Web. Half-age is proposed as a measure of the age distribution because this is found to be exponential. "Web Upda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Thus, we observed 3586 (25,3%) 2-sessions, 3188 (22,5%) 3-sessions, 2227 (15,7%) 4-sessions and so on. We also appreciated that the length distribution of sessions follows an exponential decay (Bianco et al, 2005) similar to the observed in other longitudinal web phenomena (Ortega, Cothey, & Aguillo, 2009). The fit of the distribution is high (R 2 = .98), so we may estimate the number of sessions by length not identified.…”
Section: Session Lengthsupporting
confidence: 82%
“…Thus, we observed 3586 (25,3%) 2-sessions, 3188 (22,5%) 3-sessions, 2227 (15,7%) 4-sessions and so on. We also appreciated that the length distribution of sessions follows an exponential decay (Bianco et al, 2005) similar to the observed in other longitudinal web phenomena (Ortega, Cothey, & Aguillo, 2009). The fit of the distribution is high (R 2 = .98), so we may estimate the number of sessions by length not identified.…”
Section: Session Lengthsupporting
confidence: 82%